Zircon U-Pb geochronology and heavy mineral composition constraints on the provenance of the middle Miocene deep-water reservoir sedimentary rocks in the Yinggehai-Song Hong Basin, South China Sea. (November 2016) - Wang, Ce; Liang, Xinquan; Foster, David A.; Xie, Yuhong; Tong, Chuanxin; Pei, Jianxiang; Fu, Jiangang; Jiang, Ying; Dong, Chaoge; Zhou, Yun; Wen, Shunv
Abstract: The provenance of the middle Miocene deep-water sedimentary rocks was studied by detrital zircon U-Pb ages and heavy mineral assemblages in the Yinggehai-Song Hong Basin. U-Pb age data for 936 detrital zircons from eleven sedimentary rock samples from the Meishan Formation (Langhian-Serravallian) range in age from 3252 Ma to 28 Ma and suggests input from multiple sources. The provenance of the sediments changes from one part of the basin to another. The sedimentary rocks located on northern and western Yinggehai-Song Hong Basin generally have multiple detrital zircon age populations and a wide range ages, suggesting consistent with derivation from the Red River. By contrast, the zircon ages from eastern side of the basin generally show bimodal detrital zircon age populations consisting of ca. 98 Ma and 241 Ma components, which suggest that these sandstones were derived locally from Hainan. Comparison of the age populations and heavy mineral assemblages with the potential sources terrains indicates that both southern Yangtze Block and Hainan Uplift contributed the clastic material to the basin during middle Miocene. The majority of clastic material was supplied from the northwest and east through the "Red River delta" and other deltas near to the western Hainan, respectively. Heavy mineral assemblages and zircon ages also reveal that small amounts of sediment were shed westwards from the Indochina Block. Moreover, no significant change is indicated between the Upper and Lower Meishan Formation by zircon U-Pb ages and heavy mineral data suggesting that the Yinggehai-Song Hong Basin sources were similar throughout the middle Miocene. Highlights: Detrital zircons and heavy minerals from the middle Miocene sediments were examined. The provenance of the sediments changes from one part of the basin to another. Both southern Yangtze Block and Hainan Uplift contributed the clastic material to the basin during middle Miocene. No significant change is indicated between the Upper and Lower Meishan Formation.